A Study of the Relationship Between the Geographic Locations of the User and Participation in Twitter During Different Types of News Events - Ahmed, Ghada; Watters, Carolyn (Transactions on Engineering and Computing Sciences, 2019)
Twitter is one of the most active social networks in news sharing. People report local events sometimes faster than news agencies. During major events, such as earthquakes and presidential elections, people share tweets, retweets, images and links related to the event, creating an overwhelming number of posts. The amount of data generated by social media provides a shared resource for the discovery of information for individuals, organizations and governments, but the large stream of tweets makes tracking interesting posts a challenging task. Understanding user behavior during different contexts provides substantial insight to get the most out of the social media. The objective of this work is to investigate the relationship between user participation, news type and geographic locations of Twitter’s users. The results show that financial news tweets have distinct user behavior compared to tweets about political events and tweets about disasters. Tweets about financial events tend to have more original tweets and more links, than tweets about political events, which had larger numbers of retweets. The investigation of the relationship between the style of user’s participation and the type of news provides insight for social media management, specifically, for using information diffusion proactively, real time filtering, and location-aware news recommendation systems. We found that there are relationships between the country of the user, the type of news and user tweeting behavior for news related tweets. News type is strongly correlated to users’ behavior and was found to have a stronger relationship to users’ behavior than geographic location.